El despojo y la apropiación de recursos naturales en el proceso actual de acumulación capitalista - Ortega Herrera, Jose Manuel; Pérez Martín, María Ángeles (Pùblicageografía ;, 2019)
Seven essays by social scientists about mechanisms of plunder in Latin America and their impact on capital accumulation. Organized into sections on monetization and dispossession of natural resources, historical analysis, environmental discourse, and geopolitics.